Being Human: Human-Computer Interaction in the Year 2020 - Harper, Richard; Rodden, Tom; Rogers, Yvonne; Sellen, Abigail (2008)
The question persists and indeed grows whether the computer will make it easier or harder for human beings to know who they really are, to identify their real problems, to respond more fully to beauty, to place adequate value on life, and to make their world safer than it now is.